Improvement of crushed rock by polymer and portland cement on California Bearing Ratio (CBR) under soaked condition - Chaiyaput, Salisa; Maleesee, K.; Sirikaew, U.; Artidteang, S. (My University, 2020)
The pavement consists of surface course built on the top followed by base, subbase, and subgrade, respectively. The high stresses occur at the top layer, which is placed by the expensive material with high quality, while cheaper material with low quality is placed in the lower layer, respectively. Crushed rock is normally applied as the base material, which is required to support the high stress transmission. The soil improvement techniques have become one alternative to apply for increasing the soil strength. The one technique has been wildly adopted, is called “soil cement”. On the other hand, the soil cement road is easily to damage by heavy raining and flooding, due to brittle crack behavior in Portland cement property. Consequently, polymer has high elastic modulus, is precious to solve the brittle failure problem. This paper examines the effect of concurrent use of liquid polymer and Portland cement on crushed rock as reinforced pavement base material. The strength of polymer-treated crushed rock (treated crushed rock) and ordinary crushed rock (untreated crushed rock) were characterized and compared. In strength analysis, the California bearing ratios (CBR) of untreated and treated crushed rock were determined under soaked condition to simulate post-flood pavement damage. As a result, it was found that the CBR value of the treated crushed rock has higher than the CBR values of the untreated crushed rock (approximately two times).
Keywords: Base; CBR; Crushed rock; Pavement; Polymer